ALLERGIC DISEASES IN CHILDREN: EXPANDED COMPREHENSIVE CLINICAL REVIEW (International journal of medical sciences, 2025)
: Allergic diseases constitute one of the most prevalent chronic conditions in childhood. This expanded review examines the etiology, immunopathogenesis, clinical manifestations, diagnostic methods, management options, and preventive strategies of pediatric allergic diseases. With increasing global prevalence, understanding these disorders is crucial for clinicians, researchers, and healthcare providers involved in pediatric care.